Prediksi tebal hidrodinamik lapisan tipis (film) cairan sekeliling pipa horisontal karena pengaruh aliran jatuhan (drainage) berbentuk tabir (sheet - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Liquid film thickness around a horizontal tube is one of the important parameters in the heat transfer calculation especially for a horizontal shell and tube heat exchanger. The prediction of liquid film thickness was originated by Nusselt in 1916. Since then a number of experimental and theoretical investigations have been undertaken to asses the effect of various parameters. In this work the effect of drainage inundation of the liquid from above in the form of a sheet to the liquid film thickness around the tube is proposed. This hydrodynamic analysis takes into account the momentum of the impinging liquid which was neglected by Nusselt. The result shows that this new prediction compares good with the existing experimental data.